Increased inspiratory resistance affects the dynamic relationship between blood pressure changes and subarachnoid space width oscillations - Wszedybyl-Winklewska, Magdalena; Wolf, Jacek; Swierblewska, Ewa; Kunicka, Katarzyna; Mazur, Kamila; Gruszecki, Marcin; Winklewski, Pawel J; Frydrychowski, Andrzej F; Bieniaszewski, Leszek; Narkiewicz, Krzysztof (PLoS One, 2017)
BACKGROUND AND OBJECTIVE: Respiration is known to affect cerebrospinal fluid (CSF) movement. We hypothesised that increased inspiratory resistance would affect the dynamic relationship between blood pressure (BP) changes and subarachnoid space width (SAS) oscillations. METHODS: Experiments were performed in a group of 20 healthy volunteers undergoing controlled intermittent Mueller Manoeuvres (the key characteristic of the procedure is that a studied person is subjected to a controlled, increased inspiratory resistance which results in marked potentiation of the intrathoracic negative pressure). BP and heart rate (HR) were measured using continuous finger-pulse photoplethysmography; oxyhaemoglobin saturation with an ear-clip sensor; end-tidal CO2 with a gas analyser; cerebral blood flow velocity (CBFV), pulsatility and resistive indices with Doppler ultrasound. Changes in SAS were recorded with a new method i.e. near-infrared transillumination/backscattering sounding. Wavelet transform analysis was used to assess the BP and SAS oscillations coupling. RESULTS: Initiating Mueller manoeuvres evoked cardiac SAS component decline (-17.8%, P<0.001), systolic BP, diastolic BP and HR increase (+6.3%, P<0.001; 6.7%, P<0.001 and +2.3%, P<0.05, respectively). By the end of Mueller manoeuvres, cardiac SAS component and HR did not change (+2.3% and 0.0%, respectively; both not statistically significant), but systolic and diastolic BP was elevated (+12.6% and +8.9%, respectively; both P<0.001). With reference to baseline values there was an evident decrease in wavelet coherence between BP and SAS oscillations at cardiac frequency in the first half of the Mueller manoeuvres (-32.3%, P<0.05 for left hemisphere and -46.0%, P<0.01 for right hemisphere) which was followed by subsequent normalization at end of the procedure (+3.1% for left hemisphere and +23.1% for right hemisphere; both not statistically significant). CONCLUSIONS: Increased inspiratory resistance is associated with swings in the cardiac contribution to the dynamic relationship between BP and SAS oscillations. Impaired cardiac performance reported in Mueller manoeuvres may influence the pattern of cerebrospinal fluid pulsatility.
Keywords: Young Adult; Male; Cerebrovascular Circulation; Subarachnoid Space; subarachnoidální prostor; mladý dospělý; ultrasonografie dopplerovská transkraniální; Adolescent; mozkový krevní oběh; Heart Rate; Adult; dospělí; mužské pohlaví; srdeční frekvence; dýchání; Ultrasonography, Doppler, Transcranial; rychlost toku krve; mladiství; Respiration; lidé; krevní tlak; ženské pohlaví; Humans; Blood Pressure; zdraví dobrovolníci pro lékařské studie; Female; Blood Flow Velocity; Healthy Volunteers